The Practicality and Effectiveness of Integrated Augmented Reality Car Audio System Learning Modules in Vocational Education - Mohammad Iyo Agus Setyono; Nurhayati Nurhayati; Puput Wanarti Rusimamto; Sari Edi Cahyaningrum (Center for Community Service and Science and Technology Marketing - The Institute for Research and Community Service Universitas Negeri Surabaya, 2024)
Abstract Technological developments are undergoing an increasingly rapid transformation. Revolution 4.0 which is oriented towards digitalization and IoT technology is increasingly entering the order of human life, even in all aspects of national life. Of course, the educational field needs to be able to strike a balance between the advancement of technology and the process of learning. One way is to take advantage of the existence of technology as a means of improving the quality of learning. Up until now, a lot of instructional resources and learning media have been created through cooperation with cutting-edge technology. One technology that can be implemented is augmented reality. In response to this, this research focuses on developing a car audio system learning module integrated with augmented reality in vocational education. Teachers and XII students at SMK YKP Magetan served as the study's subjects. Data were gathered using test, questionnaire, and observation techniques. 95.33% was the module validity level, according to the results. According to the study's findings, 87.67% of teachers' and students' replies to the module demonstrated practicality, which is why it was included in the very practical qualification. The effectiveness aspect showed a significant difference between the pretest and posttest results of 35 students. The results of the research show that the effectiveness of the module is 64.58%. Particularly when it comes to car audio system content, the integrated augmented reality learning module for car audio systems has a high degree of viability that makes it suitable for use in vocational education.